Deficit of Health Social Security Fund in National Health Insurance Program: A Case Study of BPJS Kesehatan - Dinil Asyrofi; I Gede Agus Ariutama (Universitas Negeri Malang, 2019)
BPJS Kesehatan was established to implement national health insurance (JKN). As mandated by PP No. 87/2013, BPJS Kesehatan manages two types of assets carried out separately, namely BPJS Kesehatan and DJSK Assets with the latest poses a more problematic deficit in its financial performance. Thus, the research focuses on the deficit occurred in the DJSK. The method utilized in this study is qualitative case study by interviewing several parties related with the funding of JKN program then processing the data using five-stage data coding. The contribution of this study is the deepening of the factors and solutions to reduce the fiscal burden. The results indicate that the factors causing the deficit include inappropriate structure of contribution-benefit scheme, adverse selection, and insurance effect. Whereas the solutions offered are to raise the contribution premium, adjust the upper limit of the insurance contribution, implement cost sharing, improve the referral system, and implement earmarking for cigarette tax.